What determines success? examining the human, financial, and social capital of jamaican microentrepreneurs - Honig, Benson (Journal of Business Venturing, 1998)
This research examines the performance of 215 informal microenterprises in Jamaica, studying the influence of human capital, social capital, and financial capital of the owners on their business profitability. Understanding the importance of particular relationships that result in successful micro-businesses is important for a number of reasons. First, among many developing countries, the growth of microenterprise provides the most visibly vibrant and growing economic activity. Although considerable effort and resources are being directed toward microenterprise promotion schemes, empirical research on the subject is quite limited. Second, economies in developing countries mirror many of the social and institutional problems existent in urban economically disadvantaged areas of the United States and other developed countries. For these areas, microenterprise may be an essential component of urban renewal and community development. This study helps in identifying important characteristics of social and individual attributes that may be relevant to those attempting to strengthen this subsector. Finally, this study seeks to provide insight into a dimension of microbusiness research for which there are limited data, specifically, the role that social capital plays among practicing entrepreneurs and owners. This research found that different structural environments, even within a singular and small economy, may considerably alter the rates of return to human, social, and financial capital. As a result, the analysis of enterprises includes segmentation according to both the usage, or not, of employees, and the sophistication of the technologies used. Several factors were determined to enhance the profitability of the businesses in all categories. Vocational training, for example, demonstrated consistently strong and positive effects. Mother’s high occupational status (a proxy for socioeconomic status) and years of experience in the business were also consistently positive and strongly associated with increasing profits. Although additional starting capital played an important role for both the businesses with and without employees, increasing amounts failed to differentiate the success of those firms that were already operating in the higher technological tier. Obtaining a small business loan acted in a similar manner, enhancing the profitability of all firms, except those segmented into a high technological tier. One interpretation of this finding is that the role of technological choice is extremely important, and appears to dwarf that of varying amounts of starting capital. Social capital, as operationalized by frequent church attendance and marital status of the owner, was found generally to increase the profitability of the business. The data demonstrate that social networks play an important role in the success of these businesses, and that conditions in the highest tier utilize social capital in a somewhat unique manner.